2019
DOI: 10.1177/0265407519867466
|View full text |Cite
|
Sign up to set email alerts
|

A comparative case study of couples programming to support relationship quality in Nepal and Rwanda

Abstract: Although intimate partner violence (IPV) is the most common form of violence against women, there is limited understanding of best practices to prevent IPV through working directly with couples and supporting quality of relationships. There are valid concerns of safely conducting research and programming with couples. Yet couples programming responds to the fact that many couples may want to stay together but require support and skills to manage violence. This article compares evaluation data of two programs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Couples who volunteer, especially for programmes requiring long-term commitments, may be more likely than others to benefit and see improvements in their relationships. 12 25 We were unable to blind participants to the study assignment at the enrolment phase, so this may have resulted in some differential recruitment between arms. While the intervention and control participants were demographically similar at baseline, the two study arms asked participants to volunteer for different tasks(participating in a 22 session curriculum versus research interviews only)which could have prompted different willingness to enrol; control participants were more likely to report that both members of the couple belonged to a VSLA, suggesting that there may have been some systematic difference in who came forward to participate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Couples who volunteer, especially for programmes requiring long-term commitments, may be more likely than others to benefit and see improvements in their relationships. 12 25 We were unable to blind participants to the study assignment at the enrolment phase, so this may have resulted in some differential recruitment between arms. While the intervention and control participants were demographically similar at baseline, the two study arms asked participants to volunteer for different tasks(participating in a 22 session curriculum versus research interviews only)which could have prompted different willingness to enrol; control participants were more likely to report that both members of the couple belonged to a VSLA, suggesting that there may have been some systematic difference in who came forward to participate.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Such approaches typically use group or community-based formats with trained facilitators rather than therapists or counsellors, and often respond to high generalised rates of IPV, as well as economic and social conditions that hinder women from leaving unsafe relationships. 12 This paper seeks to enhance the global evidence base on couples’ programming by sharing findings from an evaluation of the couples’ component of Indashyikirwa, an IPV prevention programme in Rwanda. A separate manuscript presents findings from the results from repeat cross-sectional surveys of the communities before and after the three other components of Indashyikirwa , as well as insights from the detailed process evaluation that accompanied the rollout.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in women's financial independence enhances their household position through financial contributions and control over resources, increases their household economic status, and widens their support networks (Vyas, Mbwambo, and Heise 2015). This is supported by recent evidence from a social and economic empowerment trial in Afghanistan (Gibbs et al 2020), a cluster randomised trial of women's groups in Nepal (Gram, Morrison, Saville, et al 2019) and three intimate partner violence prevention trials that included economic strengthening components plus gender training in Tajikistan, Rwanda and South Africa (Stern, McGhee, et al 2020), where women's experience of work outside the home indicates a broader transformation of their livelihood opportunities. However, the effect of income generation by itself on women's risk of violence is contingent on a number of other factors, particularly men's reactions (Agarwal 1997;Heise 2011).…”
Section: Women's Economic Empowerment and Intimate Partner Violencementioning
confidence: 88%
“…The risk of increased intimate partner violence could decline over time, however, as both men's individual attitudes and broader social attitudes become more accepting of women's increased economic activity and financial autonomy (Ahmed 2005). This was evidenced in three studies included in a Stern, McGhee, et al (2020) paper where participants reported shifts from harmful gender norms and roles towards more equitable decision-making and the sharing of household tasks and provider roles. Therefore, the relationship between women's empowerment and intimate partner violence is not straightforward and warrants further exploration (Raj et al 2018;Vyas and Watts 2009).…”
Section: Women's Economic Empowerment and Intimate Partner Violencementioning
confidence: 99%
See 1 more Smart Citation